1991
DOI: 10.1001/archsurg.1991.01410350066010
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Dietary Arginine Inhibits Growth of Metastatic Tumor

Abstract: The effects of dietary arginine on the growth of a murine colon tumor metastatic to the liver were examined in a model of advanced neoplastic disease. Tumor growth was influenced by arginine both in vivo and in vitro. An arginine-supplemented diet stimulated tumor growth by 55% compared with controls. Conversely, an arginine-depleted diet inhibited tumor growth by 78% compared with controls. In vitro culture of both murine and human colon tumor cells confirmed that arginine was necessary for cell growth. Flow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 9 publications
3
42
0
Order By: Relevance
“…For example, Gilroy in 1930 15 and Yeatman et al in 1991 16 demonstrated that mice fed an arginine-enriched diet developed tumors that grew faster and larger than mice fed a normal diet. Conversely, mice fed an arginine-deficient diet have reduced tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Gilroy in 1930 15 and Yeatman et al in 1991 16 demonstrated that mice fed an arginine-enriched diet developed tumors that grew faster and larger than mice fed a normal diet. Conversely, mice fed an arginine-deficient diet have reduced tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, mice fed an arginine-deficient diet have reduced tumor growth. 16,17 Therefore, there is a long history of evidence in the nutritional literature indicating a requirement for arginine in the growth of some tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these biologic products have been implicated in tumor development, and therefore, feeding mice with arginine enhances tumor growth (5). In contrast, depletion of dietary arginine inhibits liver metastasis (6).…”
Section: Introductionmentioning
confidence: 99%
“…Such factors include beta fibroblast proliferation-stimulating GF (FGFb), platelet-derived growth factor (PDGF), hepatocyte growth factor (HGF), and others (4)(5)(6). It is important therefore to design combined treatments that will inhibit residual tumor cell proliferation following surgery, without impairment of the healing process.…”
Section: Introductionmentioning
confidence: 99%